ECO printshop / Muhammad Aizat Mohd Adnan, Nor Alia Shahira Nazir & Nur Izzati Rahmat - Mohd Adnan, Muhammad Aizat; Nazir, Nor Alia Shahira; Rahmat, Nur Izzati (2017)
Our company always thinking about making a change to more eco-friendly products such as copiers, printers and fax machines, so this is most cost effective eco-friendly printers. When it comes to eco-friendly printers, many of the top money saving opportunities come after purchase the new hardware. We can select how we print and how much ink used. We also have ability to print on both sides of paper, the kind paper of we use and even the kind of cartridge we utilize (some brands use only recycled plastic). Chances we can alter the way it prints to improve money and eco savings.